Urinary incontinence and its association with functional physical and cognitive health among female nursing home residents in Switzerland. Issue 1 (December 2017) - Schumpf, Lea; Theill, Nathan; Scheiner, David; Fink, Daniel; Riese, Florian; Betschart, Cornelia
Abstract Background Specific knowledge of urinary incontinence (UI) and its interrelation with physical and cognitive health is essential to working towards prevention of UI and to improving quality of treatment and care. The purpose of this study was to determine the association between UI and the activities of daily living (ADL) hierarchy scale, the cognitive performance scale (CPS) and comorbid conditions. Methods The cross-sectional retrospective analysis of 357 nursing homes in Switzerland was based on data of the Minimum Data Set of the Resident Assessment Instrument 2.0 (RAI-MDS). The analysis examined the effect of ADL hierarchy scale, CPS, joint motion and comorbidities on UI. Women  ≥65 years were included (n  = 44'811; January 2005 to September 2014) at the time of admission to a nursing home. Statistical analysis was done by means of descriptive statistics and logistic regression analysis. Results The prevalence of UI was 54.7%, the mean ADL hierarchy scale (± SD) 2.42 ± 3.26 (range = 0–6), the mean CPS 1.95 ± 1.67 (range = 0–6). There was a gradual increase in the odds ratio (OR) for UI depending on the ADL hierarchy scale, from the hierarchy scales of "supervised" to "total dependence" of 1.43 – 30.25. For CPS, the OR for UI from "borderline intact" to "very severe impairment" was 1.35 – 5.99. Considering the interaction between ADL and CPS, all ADL hierarchies remained significantly associated with UI, however for CPS this was the case only in the lower hierarchies. Of the 11 examined comorbid conditions, only diabetes mellitus (OR 1.19), dementia (OR 1.01) and arthrosis/arthritis (OR 1.53) were significantly associated with UI. Conclusion The study indicated that impairment in ADL performance is strongly associated with UI, more than CPS performance and comorbidities. Physical more than cognitive training in order to improve or at least stabilize ADL performance could be a way to prevent or reduce the process of developing UI.